Lipidomic analysis reveals disturbances in glycerophospholipid and sphingolipid metabolic pathways in benzene-exposed mice. Issue 4 (15th June 2021) - Yu, Linling; Sun, Rongli; Xu, Kai; Pu, Yunqiu; Huang, Jiawei; Liu, Manman; Chen, Minjian; Zhang, Juan; Yin, Lihong; Pu, Yuepu
Abstract: Benzene, a known occupational and environmental contaminant, has been recognized as the hematotoxin and human carcinogen. Lipids have a variety of important physiological functions and the abnormal lipid metabolism has been reported to be closely related to the occurrence and development of many diseases. In the present study, we aim to utilize LC–MS/MS lipidomic platform to identify novel biomarkers and provide scientific clues for mechanism study of benzene hematotoxicity. Results showed that a total of 294 differential metabolites were obtained from the comparison of benzene-treated group and control group. The glycerophospholipid pathway was altered involving the down-regulation of the levels of phosphatidylcholine and phosphatidylserine. In addition, phosphatidylethanolamine (PE) and 1-Acyl-sn-glycero-3-phosphocholine levels were increased in benzene-treated group. Based on the relationship between PE and autophagy, we then found that effective biomarker of autophagy, Beclin1 and LC3B, were increased remarkably. Furthermore, following benzene treatment, significant decreases in glucosylceramide (GlcCer) and phytosphingosine (PHS) levels in sphingolipid pathway were observed. Simultaneously, the levels of proliferation marker (PCNA and Ki67) and apoptosis regulator (Bax and Caspase-3) showed clear increases in benzene-exposed group. Based on our results, we speculate that disturbances in glycerophospholipid pathway play an important role in the process of benzene-induced hematopoietic toxicity by affecting autophagy, while sphingolipid pathway may also serve as a vital role in benzene-caused toxicity by regulating proliferation and apoptosis. Our study provides basic study information for the future biomarker and mechanism research underlying the development of benzene-induced blood toxicity. Graphical abstract: